Metabolism of Aspartate by Propionibacterium freudenreichii subsp. shermanii: Effect on Lactate Fermentation - Crow, Vaughan L. (1986)
More than 90% of the aspartate in a defined medium was metabolized after lactate exhaustion such that 3 mol of aspartate and 1 mol of propionate were converted to 3 mol of succinate, 3 mol of ammonia, 1 mol of acetate, and 1 mol of CO(2). This pathway was also evident when propionate and aspartate were the substrates in complex medium in the absence of lactate. In complex medium with lactate present, about 70% of the aspartate was metabolized to succinate and ammonia during lactate fermentation, and as a consequence of aspartate metabolism, more lactate was fermented to acetate and CO(2) than was fermented to propionate. The conversion of aspartate to fumarate and ammonia by the enzyme aspartase and subsequent reduction of fumarate to succinate occurred in the five strains of Propionibacterium freudenreichii subsp. shermanii studied. The ability to metabolize aspartate in the presence of lactate appeared to be related to aspartase activity. The specific activity of aspartase increased during and after lactate utilization, and the levels of this enzyme were lower in cells grown in defined medium than levels in those cells grown in complex medium. Under the conditions used, no other amino acids were readily metabolized in the presence of lactate. The possibility that aspartate metabolism by propionibacteria in Swiss cheese has an influence on CO(2) production is discussed.